PERTIMBANGAN FISIOGRAFIS DALAM PENGEMBANGAN WILAYAH KUBAH GAMBUT (STUDI KASUS: KAWASAN STRATEGIS LUNANG SILAUT SUMATERA BARAT) - hamdi nur; Ahyuni ahyuni (Jurusan Geografi Fakultas Ilmu Sosial Universitas Negeri Padang, 2015)
ABSTRACT Regional development needs to consider the region as a physiographic unit. Development of peat swamp region especially in peat dome physiographic group for agricultural activities and settlement has various limitations and vulnerabilities with the consequences that should be considered in development planning. This study examines the case of development of Lunang Silaut region that have the characteristics of peat dome physiography. This region is one of economic strategic region of West Sumatra Province and as a location of “Kota Terpadu Mandiri” (KTM) which is a program of the Ministry of Manpower and Transmigration to promote backward region development. From the case, subsequently various considerations concluded for the development planning of peatdome region